PENERAPAN METODE TGT (TEAM GAME TOURNAMENT) MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS PADA SISWA KELAS VIII DI SMP NEGERI 1 BANDAR BARU - Nasruddin Nasruddin (Jurnal Sains Riset, 2019)
This study aims to determine the increase in learning motivation which in turn will improve student learning outcomes in learning Class VIII English with the application of TGT (Team Game Tournament) on the self-test unit material at Bandar Baru 1 Junior High School, second semester 2015/2016 academic year .This type of research includes action research. The subjects of this study were Class VIII students at SMP Negeri 1 Bandar Baru. The results of this study indicate: Through the results of classroom action research at SMP Negeri 1 Bandar Baru there was an increase in learning motivation, namely in the first cycle the average was 68.10 while in the second cycle was 80.00. Before learning with the TGT (Team Game Tournament) Method, the student score is 60.71. In the first cycle, the results of student evaluations in the eyes of English Language Subjects The self-test unit gets an average score of 70.00, while in the second cycle it gets an average score of 80.00. From the study there was an increase in learning completeness as much as in the first cycle of 33% and in the second cycle by 95%. Thus, it can be concluded that the implementation of classroom action research through the TGT (Team Game Tournament) Method of learning English in the material The self-test unit can increase learning motivation which by itself can improve learning outcomes for Class VIII students at SMP Negeri 1 Bandar Baru. Keywords: TGT Method (Game Tournament Team), Learning Outcomes